Concomitant case of thyroid nodule with parathyroid adenoma - a case report - Tambat, Ramesh Mahadev; Rao, R. Rajashekhar; Kulkarni, A. V.; S., Rekha V.; Bhattacharya, Anchita (International Surgery Journal, 2021)
Coexistence of PHPT in patients with thyroid nodules can complicate patient management if associated with undetected hypercalcemia or unrecognized thyroid cancer. It is an uncommonly diagnosed condition, due to overlapping symptoms in developing countries like India and almost all patient get symptomatic treatment. A 47-year-old female patient presented a history of progressively increasing swelling in the thyroid region associated with continuous dull ache and whose was diagnosed as thyroid nodule with parathyroid adenoma. Thyroidectomy with parathyroidectomy is the preferred modality of treatment for thyroid disorder with additional parathyroid adenoma. The thyroid nodules should be carefully evaluated during the preoperative work-up of a patient with primary hyperparathyroidism. Both MIBI and neck USG should be done in the evaluation of patients undergoing thyroidectomy and parathyroid excision simultaneously to locate the parathyroid adenomas.